A REVIEW OF SHARIAH PRINCIPLE APPLIED FOR TAKAFUL BENEFITS PROTECTION SCHEME AND ITS APPLICATION BY MALAYSIAN DEPOSIT INSURANCE COOPERATION (PIDM) - Mohd. Noor, Azman; Haron, Muhamad Nasir (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2018)
Takaful and Insurance benefits protection scheme is an innovative product introduced by the Malaysian Deposit Insurance Coporation (PIDM) to provide takaful certificate and insurance policy owners with an explicit protection against the loss of part or all of their benefits in the event of an insurer member failure. The main objective of takaful and insurance benefits protection is to promote public confidence in Malaysia’s financial system by protecting takaful certificate and insurance policy owners against the loss of their benefits. This paper reviews the possibility of implementing al-kafalah bi al-ajr, or charging fee from or a guarantee from Shari’ah perspective. It also attempts to explore other possible viable alternative instrument in compliance to Shari’ah principles. Any issues and recommendations in this paper are intended to provide positive and constructive improvement for the benefit of the Islamic finance industry.